The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/hnp.0000000000000105
|View full text |Cite
|
Sign up to set email alerts
|

The Use of ShotBlocker for Reducing the Pain and Anxiety Associated With Intramuscular Injection

Abstract: There are few studies evaluating the effect of ShotBlocker on pain acquired from intramuscular injection, and these are mostly in children. We hypothesized that the use of ShotBlocker, while administering an intramuscular injection, would reduce the pain and anxiety due to intramuscular injection in adults. A randomized, placebo controlled trial was carried out for more than 20 months in 2010-2011 on 180 adults aged 18 to 80 years who received intramuscular injections of diclofenac sodium (75 mg/3 mL) at the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
4
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(112 citation statements)
references
References 20 publications
6
97
4
5
Order By: Relevance
“…The five RCTs (Barnhill et al, ; Çelik & Khorshid, ; Kara & Yapucu Güneş, ; Rock, ; Yilmaz, Khorshid, et al, ) provided detailed information about the randomization process. These studies had low random sequence generation bias; bias with the other study was unclear (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The five RCTs (Barnhill et al, ; Çelik & Khorshid, ; Kara & Yapucu Güneş, ; Rock, ; Yilmaz, Khorshid, et al, ) provided detailed information about the randomization process. These studies had low random sequence generation bias; bias with the other study was unclear (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies (Alavi, ; Barnhill et al, ; Çelik & Khorshid, ; Chung et al, ; Yilmaz, Khorshid, et al, ) had high‐risk levels of bias. In one study, there was no blinding of the patients and personnel (Alavi, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The VAS is the most widely used (one-dimensional) tool for measuring pain around the world [24]) using a straight 10-cm line representing the words "no pain" at the left-most end and "worst pain imaginable" at the right-most end. The patients mark this line according to the extent of their pain, and then a numerical representation of their pain severity is determined by measuring the distance between the left-most end and the point where the patients have marked [25]. This tool has been widely used in national and international studies and its validity and reliability have been demonstrated [12].…”
Section: Methodsmentioning
confidence: 99%
“…Since IM injection pain results from damage to the tissue and is one of the most common complications of IM injection, it should not be underestimated. [ 3 5 6 7 ] Although many studies have addressed pharmacological and nonpharmacological methods of IM pain reduction,[ 6 ] research continues to find more effective techniques to reduce it. [ 8 ] Since applying new techniques of IM injection and creating an enjoyable experience are of the ethical and legal duties of nurses,[ 5 ] gaining skill in injection based on most recent studies has long been considered by nursing science.…”
Section: Introductionmentioning
confidence: 99%